Guardianship of Life: Islam’s Stand on Human Sanctity - Ali Muhammad Bhat (PT. Radja Intercontinental Publishing, 2025)
The foundational principles of human rights in Islam are inherently linked to essential entitlements such as the right to life, protection from forced labour, the right to own property, and freedom of expression. Both religious and secular worldviews have historically influenced the legal frameworks that govern human rights. Despite being regarded as inherent and inviolable, these rights have been frequently violated, resulting in the suffering and death of countless individuals through acts of cruelty and injustice. In response to the atrocities of World War II, the United Nations General Assembly formulated and adopted the Universal Declaration of Human Rights (UDHR), marking a significant step in the global acknowledgement of these rights. However, the Western approach to human rights has often differed in terms of interpretation, implementation, and access. The evolution of human rights is, in essence, a continuous discourse on what constitutes the inherent dignity and rightful entitlements of the human being. Ideally, such rights should be considered universal and beyond dispute. Recognizing this, I found it imperative to emphasize the significance of human dignity and property rights from an Islamic standpoint.